Analysis of User Satisfaction on the Shopeepay Application by Using the Usability Method - Fitriasari Fatinah (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This study aims to analyse the level of user satisfaction with the ShopeePay digital wallet application using the Usability method. This method has five variables to evaluate the level of user satisfaction, namely Learnability, Efficiency, Memorability, Errors, and Satisfaction. Data was collected through a questionnaire of 262 data with case study specifications on Sriwijaya University students. The reason for the research is because of the population and diversity of Sriwijaya University students from various faculties and regions who study at Sriwijaya University. The results of the analysis show that the usability method applied contributes significantly to user satisfaction. The variables that have been set show positive and negative influences from users. The Shopee Pay application analysed aims to measure the level of user satisfaction, by understanding the factors that influence customer satisfaction to maintain the quality of the ShopeePay digital wallet (e-wallet) service.